Relationship of sleep quality, perceived stress and creativity among undergraduates in Malaysia - Chiew, Yong Nuo; Logish, Baskaran; Tan, Wei Hou (2022)
There is a paucity of research on the relationship between sleep quality, and perceived stress towards creativity among Malaysian undergraduate students. This study proposed to determine the relationship of sleep quality, perceived stress, and creativity among the undergraduate students in UTAR and creativity level among the undergraduate students in UTAR was explored. In this thesis, two hypotheses were constructed which assume there is a significant relationship between sleep quality and creativity; there is a significant relationship between perceived stress and creativity. This thesis used cross-sectional design, and convenience sampling method to get the data. A total of 140 people was reached after the survey was sent to undergraduates, age from 18- 24 years old through WhatsApp, Microsoft Team, and QR code. The number of male respondents is 67 and female respondents are 75 with majority of them are Chinese, followed by Indian, Malay, and Punjabi. The research location was conducted at UTAR Kampar Campus, Perak. Next, the scales involved are Sleep Quality Scale (SQS), Perceived Stress Scale (PSS), Self-rated Creativity Scale (SRCS) and analyzed by Pearson Correlation Coefficient. The result reported the non-significant relationship of sleep quality and creativity. However, a significant negative relationship was found between perceived stress and creativity. In conclusion, this study provided a new insight towards the creativity area and the people who suffer from stress. Future researchers are encouraged to use mixed methods to achieve better results.